Agentes de mudança, contextos políticos & dinâmica institucional : um estudo sobre o processo de mudança institucional gradual no setor da segurança pública no Brasil - Íris Gomes dos Santos (2015)
The present doctorate thesis aims to explain the process of institutional change in the public security sector. I observe under what conditions of interaction among the political scenario, actors and endogenous elements of institutions, changes and institutional dynamism take place. Constitutional institutions in the public security sector present high stability. Notably, police bureaucracy has great autonomy mainly because they are institutional actors who possess veto power. The main goal of this research is to answer how and why institutional changes were achieved in the public security sector between 1989 and 2014 despite the stability of macro institutional rules. The primary hypothesis is that in such contexts featuring multiple interests and veto-points, institutional change occurs in a slow and gradual way, not through amendments or alteration on macro rules but through actions undertaken by political agents who actively explore gaps and ambiguities inherent to institutions, interpreting structures of constraints and opportunities in a different way in order to convert them to serve to new functions or purposes. This hypothesis is based on premises of the Theory of Gradual Institutional Change which seeks to integrate agency and structural elements, highlighting the importance of identities and coalition formation, rule interpretation and ideas. Under this perspective, changes are less abrupt and disruptive than the result of a gradual and endogenous process deriving from the institutional structure itself, from the gaps and ambiguities on its design created over time through a process of interpretation, dispute and targeting in this policy implementation. Using a process tracing methodology, I initially analysed the institutional legacy of the Military Dictatorship, as well as traced sources of ideas, arenas and ideologies placed in the National Constituent Assembly. This work has been done seeking to further our understanding on the corporatist and conservative tendencies present on institutions of this sector. Then, I analysed current constitutional rules according to elements of their institutional syntax in order to identify gaps and ambiguities which allowed the efforts for changing in the New Republic. Through the identification of the structure of constraints and incentives underlying the focused institutions, and after examining constitutional amendments (approved, rejected and archived), as well as considering Laws created after 1988 and the main public policies implemented, I observed that the flow of new ideas resulting from the growing of epistemic communities and the alliance between governs and scholars were decisive factors for the formation of coalitions able to process a gradual movement to sophisticate public security policies. The continuity of such policies, investments and the strengthening of intergovernmental relations incurred on a path of gradual changing and forced the creation of new rules at the intermediate level directed to the fulfilment of constitutional gaps, that follows new logics of action.